Optimizing Islamic Religious Education Teachers' Strategies in Addressing the Moral Crisis of Students in the Society 5.0 Era - Sartika Mahmud; Burhanudin Abdul Karim Mantau; Lukman Arsyad (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2026)
This study aims to analyze in depth the optimization of Islamic Religious Education teachers' strategies in overcoming the moral crisis of students in the Society 5.0 era at SMA Negeri 1 Pinolosian. The study used a qualitative approach with a case study design, while data were collected through observation, in-depth interviews, and documentation studies with the principal, Islamic Religious Education teachers, students, and parents. Data analysis was carried out interactively using the Miles, Huberman, and Saldaña model, while data validity was guaranteed through triangulation of sources, techniques, and time. The results of the study indicate that the optimization of Islamic Religious Education teachers' strategies is implemented through the integration of exemplary behavior (uswah hasanah), habituation of religious values, strengthening school culture, mentoring students, collaboration with families, and the use of digital literacy based on Islamic ethics so as to strengthen the internalization of students' moral values ​​amidst the challenges of the Society 5.0 era. The conclusion of the study confirms that the effectiveness of moral development is not only determined by the learning process in the classroom, but also by the synergy between schools, families, and the digital environment in building an educational ecosystem that supports character formation. The novelty of this research lies in the development of a model for optimizing Islamic Religious Education teacher strategies based on a pedagogical-religious ecosystem, which integrates pedagogical, religious, social, and digital literacy dimensions as a unified strategy for moral development. This model contributes scientifically to the development of Islamic Religious Education theory and offers a conceptual model that can be used as a reference in developing policies and practices for fostering student moral development in the Society 5.0 era.